The volume of the thalamus and hippocampus in a right-handed female episodic migraine group - He, Mingchen; Kis-Jakab, Gréta; Komáromy, Hedvig; Perlaki, Gábor; Orsi, Gergely; Bosnyák, Edit; Rozgonyi, Renáta; John, Flóra; Trauninger, Anita; Eklics, Kata; Pfund, Zoltán (Frontiers in Neurology, 2023)
Background/aim Migraine is a disabling headache with clinical and radiological complications. The aim of this study was to investigate the volume of the thalamus and hippocampus in migraineurs, the role of white matter lesions (WMLs), and the migraine characteristics in volume changes. Methods Brain MRIs of 161 right-handed female episodic migraine patients and 40 right-handed, age-related, healthy women were performed. Left and right thalamus segmentation was performed on the 3D MPRAGE images using the Freesurfer 5.3 image analysis suite. Hippocampal subfield segmentation was based on a novel statistical atlas built primarily upon ultra-high-resolution ex vivo MRI data. Results The left hippocampus had a smaller and the left thalamus had a larger total volume than the right one in both the control (p < 0.001) and migraine groups (p <0.001). Patients with white matter lesions (L+) showed smaller right thalamus and right hippocampal tail volumes than patients without lesions (L–) (p = 0.002 and p = 0.015, respectively) and controls (p = 0.039 and p = 0.025, respectively). For the right hippocampal body, we found significantly smaller volume in L+ patients when compared to L– patients (p = 0.018) and a similar trend when compared to the control group (p = 0.064). Patients without aura (A–) showed a larger right hippocampus (p = 0.029), right hippocampal body (p = 0.012), and tail volumes (p = 0.011) than patients with aura (A+). Inverse correlations were found between attack frequency and the volumes of the left and right hippocampal tails (p = 0.018 and p = 0.008, respectively). Conclusion These findings indicate that WMLs may influence the volume of the right thalamus and hippocampus, while migraine aura and attack frequency may lead to volume changes in different parts of the hippocampi in migraine patients. These data support the necessity of effective migraine management to limit subcortical volume loss in migraineurs.